1993
DOI: 10.1136/jnnp.56.11.1178
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral neuropathy associated with monoclonal IgM anti-Pr2 cold agglutinins.

Abstract: A patient with a chronic, large fibre sensory neuropathy had an immunoglobulin MB monoclonal paraprotein reactive at titres in excess of 1/105 with NeuNAc(a2-8)NeuNAc(a2-3)Gal configured disialosyl groups present on the gangliosides GDlb, GTlb, GQlb, and GD3. The paraprotein showed weaker reactivity with GDla, GM3, and LM1 but no reactivity with GM2, GM1, or asialo-GM1. In addition, the paraprotein had cold agglutinating activity with anti-Pr2 specificity, Pr2 being an antigenic determinant on membrane glycopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

1994
1994
1999
1999

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 23 publications
1
44
0
Order By: Relevance
“…Ha1 binding to gangliosides was shown to be highly temperature dependent, being greater at 4 Њ C than at 20 Њ C (room temperature) or 37 Њ C (body temperature), as previously noted for the serum and rbcM (19). In addition, Ha1 agglutinated human red blood cells in the cold (4 Њ C) with a hemagglutination titre (as expressed in milligrams of IgM) identical to that of the rbc-M fraction (data not shown).…”
Section: Characteristics Of the Mab Ha1 And Identity Of Ha1 To The Sementioning
confidence: 61%
See 3 more Smart Citations
“…Ha1 binding to gangliosides was shown to be highly temperature dependent, being greater at 4 Њ C than at 20 Њ C (room temperature) or 37 Њ C (body temperature), as previously noted for the serum and rbcM (19). In addition, Ha1 agglutinated human red blood cells in the cold (4 Њ C) with a hemagglutination titre (as expressed in milligrams of IgM) identical to that of the rbc-M fraction (data not shown).…”
Section: Characteristics Of the Mab Ha1 And Identity Of Ha1 To The Sementioning
confidence: 61%
“…Fourthly, using this approach one can assess the conduction in individual nerves by measuring spontaneous and evoked neurotransmitter release at individual neuromuscular junctions. Fifthly, even though the patient Ha's symptoms were predominantly sensory rather than motor, clinical neurophysiological assessment indicated that nerve conduction was markedly reduced in motor nerves (19). Although justifying our use of a motor preparation, we recognize the important need in future work to extend our physiological studies to include sensory nerve preparations to draw more clinically relevant pathophysiological conclusions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reactivity of anti-Pr CA with gangliosides has been investigated by Uemura et al [4] by thin-layer chromatog gliosides containing disialosyl groups (GDlb, GTlb, GQlb and GD3) and which have no activity for GM1 have been identified in 5 patients with predominantly sensory neuro pathies [10][11][12][13][14]. The clinical and serological findings for this group of patients have recently been reviewed [14].…”
Section: Introductionmentioning
confidence: 99%